The Effect Of Oil Pulling Using Coconut Oil On Gingival Condition In USU Dental Students - Nasution, Aini Hariyani; Rahmahwati, Dwi Rizki (IIUM Medical Journal Malaysia, 2017)
Introduction: Oil pulling is one of the adjunct oral hygiene procedure which is done by gargling with vegetable oil, such as coconut oil. Coconut oil is used due to its bioactive substances such as tocopherols, tocotrienols, and flavonoids, saturated fatty acid such as caprylic, capric, and lauric acid, and also unsaturated fatty acid such as oleic and linoleic acid.The aim of this study was to evaluate the effect of gargling with oil pulling method using coconut oil on plaque accumulation and gingival inflammation. Materials and Methods: The design of this experimental study is prepost test control group design. A total of 40 subjects from USU dental students was chosen by simple random sampling technique according the inclusion and exclusion criteria and then divided into two groups. The experimental group was asked to gargle with oil pulling method using coconut oil while the control group was asked to do daily oral hygiene procedure. Assessment was done on day 0 and day 10 using Löe and Silness plaque and gingival indices. The data was analyzed by using unpaired and paired t-test. Results: Results show a reduction in plaque and gingival scores from day 0 until day 10, which are 0.248 ± 0.139 (p<0.05) and 0.283 ± 0.168 (p<0.05) respectively. Conclusion(s): In conclusion, oil pulling using coconut oil effectively reduces plaque accumulation and gingival inflammation.